Investigation of Transferable Skills’s Vocational Teachers in Terms of Work Culture and Age - Purnomo Purnomo (BRILIANT: Jurnal Riset dan Konseptual, 2021)
This research is a quantitative study using an ex-post facto design. The sample of 102 teachers using simple random sampling technique. Data collection uses questionnaires to measure work culture and age and perceptions of transferable skills. . This study aims to (1) determine the influence of work culture and age with the perception of transferable skills of productive teachers in TKI study programs in Malang City and Malang Regency and Batu City; (2) knowing the influence of work culture with the perception of transferable skills of productive teachers in TKI study programs in Malang City and Malang Regency and Batu City; and (3) knowing the effect of age with the perception of transferable skills of productive teachers in TKI study programs in Malang City and Malang Regency and Batu City. The results of this study include: (1) there is a significant influence of work culture and age with productive teacher transferable skills in Malang City and Malang Regency and Batu City; (2) there is a significant influence of work culture with productive teacher skills transferables perceptions in Malang City and Malang Regency and Batu City; and (3) there is a significant influence of teacher age with perceptions of transferable skills of productive teachers in Malang City and Malang Regency and Batu City. It can be concluded that the variable that has the highest influence is training experience.